1993
DOI: 10.1007/bf00316466
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effect and plasma concentrations of codeine and morphine after two dose levels of codeine following oral surgery

Abstract: A double blind randomised cross over investigation was carried out in 25 male patients undergoing two oral surgical extractions, one for each lower wisdom tooth. The two extractions were performed about 6 weeks apart and were carried out under local anaesthesia. One hour after each extraction the patients randomly received 90 or 45 mg codeine. During the following 5 h the patients rated the intensity of their pain on a visual analogue scale. Blood was simultaneously sampled and assayed for codeine and its meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…Clinical effects of codeine not accounted for by plasma morphine had been observed in experimental studies after oral codeine doses of 100 mg, 9 170 mg, 10 and 50 mg 13 . In the clinical setting some effects of codeine apart from morphine formation 11 were reported after 90 mg oral codeine. To administer a dose in the range of the doses after which the effects aimed for in this study had been observed, subjects first received codeine as an oral solution (ct‐Arzneimittel, Berlin, Germany) at doses initially set at a base level of 80 mg codeine but later increased to 120 mg because of small miotic effects in the first subjects.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Clinical effects of codeine not accounted for by plasma morphine had been observed in experimental studies after oral codeine doses of 100 mg, 9 170 mg, 10 and 50 mg 13 . In the clinical setting some effects of codeine apart from morphine formation 11 were reported after 90 mg oral codeine. To administer a dose in the range of the doses after which the effects aimed for in this study had been observed, subjects first received codeine as an oral solution (ct‐Arzneimittel, Berlin, Germany) at doses initially set at a base level of 80 mg codeine but later increased to 120 mg because of small miotic effects in the first subjects.…”
Section: Methodsmentioning
confidence: 98%
“…However, inhibition of CYP2D6 by quinidine did not always completely extinguish the analgesic effects of 100 mg codeine despite a very low plasma morphine concentration 9 . Subjects with nonfunctional CYP2D6 had side effects from 170 mg codeine, 10 and in 4 patients with an inability to O ‐demethylate codeine, an analgesic effect of 90 mg codeine after dental surgery was reported 11 . In addition, codeine was proposed to produce cognitive impairment independent of measurable blood morphine concentrations 12 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…22 Studies have demonstrated that only a small percentage of the total dose (3%) 23 is converted by CYP2D6 to morphine. A weak analgesic, codeine is similar in structure to morphine but has affinity for the µ-opioid receptor that is 300 times lower.…”
Section: Codeinementioning
confidence: 99%
“…The efficacy of codeine is further confounded by large interindividual and interethnic differences in demethylation capacity. Variable expression of the enzymes involved in the biotransformation of drugs can lead to substantial differences in the production rate and plasma concentration of metabolites, and hence, the efficacy of a pro‐drug (Quilding et al ., 1993; Williams et al ., 2002). The enzyme that catalyzes the demethylation of codeine to morphine is cytochrome P‐450 CYP2D6.…”
Section: Codeine Phosphatementioning
confidence: 99%